PELATIHAN DAN PENDAMPINGAN PENINGKATAN PANGSA PASAR DENGAN MODEL KEPUASAN PENGIRIMAN PESANAN KONSUMEN OBAT PADA APOTEK DI SURAKARTA - Siti Fatonah; Lukman Ahmad Imron; P. Haryoso Haryoso (Adi Widya : Jurnal Pengabdian Masyarakat, 2021)
The pharmacy was established with the aim of being able to provide good pharmaceutical services to the community including being ready to provide drug consultation, supply of drugs and pharmaceutical supplies of good quality. Therefore, pharmacies need to innovate in carrying out promotional activities to provide information and attract people to want to buy and become loyal drug consumers. One of the factors influencing a pharmacy is that how the pharmacy can provide consumers to order drugs and receive goods easily, quickly, safely and comfortably. The Community Service Team of STIE AUB Surakarta wants to socialize and train and assist to create a drug consumer satisfaction model through improving the quality of order delivery to expand the drug market in large family pharmacies in Surakarta. The size of this Community Service activity can be seen from the output in the form of 1) Pharmacy survey in improving the quality of order delivery, 2) creation of order delivery models, 3) increased pharmacy market supply, 4) scientific articles. The problems that arise by partners are 1) the quality of drug order delivery has not been maximized, 2) there are no innovations in delivery models, 3) the market is still limited. The stages of the implementation of the service carried out by the team are socializing to the community in the process of ordering and sending drugs at pharmacies in Surakarta, training partners / pharmacies in creating order delivery models and training marketing management theories to partners in order to innovate wider markets. The results expected by the team are customer satisfaction and loyalty. The next stage is the evaluation of the results of quality delivery assistance, delivery models and expansion of the pharmacy market Keyword : Quality, Order Delivery Model, Market Share